Numerical treatment to a water-quality measurement model in an opened-closed reservoir - Kraychang, Witsarut; Pochai, Nopparat (My University, 2015)
Measuring the water quality in water sources or the Monkey Cheeks Project with opened-closed reservoir. It can be measured by the field measurement, using the water quality monitoring tools and the water quality models consist of hydrodynamic model and dispersion model, to calculate the quality of the water. Hydrodynamic model, using the shallow water equation as a governing equation, is used to describe the water current, having source of wave maker and bottom topography as the required data, bringing about the elevation and velocities of water. Dispersion model, using the advection-diffusion equation as the governing equation, is used to describe the spread of the pollutant concentration of water, having pollutant concentration at point source and calculated water velocities from the first model as the input data, bringing the time-dependent pollutant concen- tration of water at any point. In this research, the three-dimensional surface fitting technique is employed, the anisotropic bottom topography data is represented by a surface function in the hydrodynamic model, in order to have a more realistic water current and water quality approximations in opened-closed reservoir.
Keywords: Advectiondiffusion equation; Dispersion model; Hydrodynamic model; Opened-closed reservoir; Water quality model